The science and technology of flexible packaging : multilayer films from resin and process to end use - Morris, Barry A.; ScienceDirect eBooks (Oxford, United Kingdom : Elsevier Ltd. : William Andrew, 2017)
Providing a comprehensive guide to the use of plastic films in flexible packaging, covering scientific principles, properties, processes, and end use considerations, this book brings the science of multilayer films to the practitioner in a concise and impactful way, presenting the fundamental understanding required to improve product design, material selection, and processes. --
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed September 15, 2016).
Elsevier
Keywords: Flexible packaging; TECHNOLOGY & ENGINEERING / Technical & Manufacturing Industries & Trades; Flexible packaging; Electronic books